Street-level climate action: a landscape based approach to investigate transportation emissions and green infrastructure solutions - Wang, Jiajia; Tao, Zhihan; Deal, Brian (Frontiers in Built Environment, 2025)
While climate change demands urgent global action, emission reduction effectiveness hinges on local implementation. This study develops a landscape planning framework for analyzing street-level transportation emissions using integrated geospatial analysis, transportation analytics, and landscape metrics. Using 2016 NLCD land cover data, 2021 census data, and 2023 IDOT traffic data for Cook County, Illinois, we quantify transportation emissions at a fine scale and identify local mitigation opportunities. Our results indicate that arterial roads generate 52.04% of transportation emissions despite lower per-meter intensity than highways. Shannon’s entropy (land use fragmentation measure) reveals downtown districts (0.586) have lower per capita emissions than fragmented suburban areas (0.951). Married households correlate with higher emissions (r = 0.302, p < 0.001) while renter-occupied areas show lower emissions (r = −0.294, p < 0.001). We also find that strategic green infrastructure implementation along arterial corridors could sequester at least 360,000 tons CO2 annually. This framework provides actionable strategies for translating global climate goals into neighborhood-scale interventions by integrating transportation planning with ecosystem services.